History of Risky Pregnancies and Failure of Exclusive Breastfeeding in Indonesia - Demsa Simbolon; Nur Mahdiyah Merly Yanti; Lisma Ningsih (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
The coverage of exclusive breastfeeding for infants in Indonesia still needs to be higher compared to the national target (80%). Low coverage of exclusive breastfeeding is a risk factor for various nutritional problems in toddlers. The causes of failure of exclusive breastfeeding are multifactorial, including risky pregnancy. This study aims to determine the association of risky pregnancies with the failure of exclusive breastfeeding using national data from the 2017 Indonesian Health Demographic Survey (IDHS) with a cross-sectional design. The study sample that met the criteria was 6,689 mothers with children aged 6-23 months. The independent variable is risky pregnancy (parity, pregnancy spacing, age during pregnancy), and the dependent variable is the failure of exclusive breastfeeding. Data analysis using multivariate logistic regression. The results found that only 26.2% of exclusive breastfeeding practices. Risky pregnancy is associated with the failure of exclusive breastfeeding. Mothers with too much parity risked 1,195 times, mothers with primiparous parity risked 1,716 times, too close birth spacing risked 1,210 times, and too young mothers were 1,267 times more likely not to exclusively breastfeed than mothers who had normal pregnancies after controlling for the area of residence. It is necessary to improve health promotion programs to the public regarding the importance of offering exclusive breastfeeding to infants and improving fertility characteristics.